Palladium-catalyzed three-component radical-polar crossover carboamination of 1,3-dienes or allenes with diazo esters and amines - Liu, Geng-Xin; Jie, Xiao-Ting; Niu, Ge-Jun; Yang, Li-Sheng; Li, Xing-Lin; Luo, Jian; Hu, Wen-Hao (Beilstein Journal of Organic Chemistry, 2024)
Herein, we report a visible-light-mediated palladium-catalyzed three-component radical-polar crossover carboamination of 1,3-dienes or allenes with diazo esters and amines, affording unsaturated γ- and ε-amino acid derivatives with diverse structures. In this methodology, the diazo compound readily transforms into a hybrid α-ester alkylpalladium radical with the release of dinitrogen. The radical intermediate selectively adds to the double bond of a 1,3-diene or allene, followed by the allylpalladium radical-polar crossover path and selective allylic substitution with the amine substrate, thereby leading to a single unsaturated γ- or ε-amino acid derivative. This approach proceeds under mild and simple reaction conditions and shows high functional group tolerance, especially in the incorporation of various bioactive molecules. The studies on scale-up reactions and diverse derivatizations highlight the practical utility of this multicomponent reaction protocol.
Keywords: carboamination; diazo chemistry; palladium catalysis; radical-polar crossover; three-component reaction